Finding the cell intrinsic mechanisms of resistance to oncogenesis - Nóbrega, Henrique Miguel Ribeiro de (2024)
Even though cancer is an ever-increasing presence in our daily lives, there are still features about cancer development that remain elusive. Some cell types are more prone to develop hyperplasia, while others present an intrinsic resistance to oncogenic stimuli. Drosophila melanogaster eye imaginal discs are a good model system to study cell sensibility to oncogenes, as cell populations in distinct differentiation states co-exist in the same tissue. Overexpression of a constitutively active oncogene (Ykiˢᴬ) promotes overgrowth in the more differentiated domains of the eye disc (Morphogenetic furrow and differentiated domain), while unspecialized progenitor cells seem to be irresponsive to the oncogenic stimuli. The main goal of this work is to understand the factors governing progenitor cells’ resistance to Ykiˢᴬ stimuli. Our hypothesis postulates the existence of a progenitor specific repressive factor that might inhibit cellular response to Ykiˢᴬ. To verifie this hypothesis, we tested whether the overexpression of progenitor specific factors could suppress Ykiˢᴬ mediated overgrowth in the eye disc domains responsive to this oncogene (MF and differentiated domains). Interestingly, we found two genes (Upd3 and Optix) that could suppress Ykiˢᴬ overgrowth in one of the differentiated domains but synergized with Ykiˢᴬ and enhanced the overgrowth in the other domain, reinforcing the idea that the context dictates the cellular response to oncogenes. Moreover, additional cellular constituents might play a role in preparing the cells for mitogenic signals. We have found that genes involved in mitochondrial homeostasis suppressed the overgrowth induced by Ykiˢᴬ and that the progenitor domain presents a less developed mitochondrial network. These results suggest that the mitochondrial organization might contribute to regulate cellular response to Ykiˢᴬ activation. Our findings provide new clues about the cellular and molecular mechanisms underlying the cellular predisposition to oncogenic transformation.